Kazakhstan in the multiverse of the 21st century: six dilemmas to draw its future path (Journal of Philosophy Culture and Political Science, 2023)
Kazakhstan Strategy-2050 outlined an ambitious development plan aimed at bringing the country into the top 30 most developed countries in the world. Nonetheless, certain unresolved issues in public governance, international affairs, economic development, national identity, the rule of law, and the center-periphery dialectic continue to conceal Kazakhstan's future steps. Therefore, this article aims to provide a critical and systemic analysis of the future of Kazakhstan, challenging the linear interpretation often offered in previous studies. Through the lens of a future triangle, this article examines six fundamental dilemmas that will have a significant impact on Kazakhstan's future development. Methodologically, it combines a critical analysis of academic resources with direct observation of local practices to draw a continuity and a transformative scenario for each of the dimensions examined in this text. What emerges is a volatile, dynamic, and uncertain framework in which a dominant national narrative may emerge, but several diverse and overlapping plots will continue to characterize Kazakhstan's storyline. Being aware of such "murky areas" is thus a necessary condition for researchers to gain a deeper understanding of contemporary Kazakhstan and its still-changing future development plans.Keywords: foresight, future triangle, Kazakhstan, Kazakhstan strategy 2050; multiverse.